Post-operative assistance in patients submitted to heart surgery (Research, Society and Development, 2022)
Cardiac surgery is indicated when the probability of survival is greater with surgical treatment than with medical treatment. It is considered large, and the most common are reconstructive, which include myocardial revascularization and valve plastic surgery, are complex interventions and require adequate treatment in all operative phases. The objective is to evaluate the assistance in the PO of cardiac surgery. This is an integrative review study, a search was carried out in the following databases: SciELO, LILACS and IBECS. Descriptors were used: "Chest surgery" and "Postoperative period". The inclusion criteria were: articles available online, in Portuguese, English and Spanish, in the years 2015 to 2022. As exclusion criteria: articles that did not cover the theme and repeated studies in the databases. From the initial search with the descriptors and Boolean operator defined, 231 studies were found in the selected base and after applying the inclusion and exclusion criteria, 13 studies were selected to compose the review. provided to the patient who undergoes cardiac surgery, regardless of the type, are extremely important because it can avoid several complications that will worsen their prognosis, so all health professionals must be aware of what happens to patients in the immediate postoperative period, being able to avoid future injuries, being the main one is death.